Radiofrequency Turbinoplasty for Nonallergic Rhinitis in Geriatric Patients. Issue 5 (September 2015) - Yu, Myeong Sang; Kang, Sung-Ho; Kim, Bo-Hyung; Lim, Dae Jun; Kim, Jong-Yeup
Background and Objective: Radiofrequency (RF) turbinoplasty may be effective in treating nonallergic rhinitis in elderly patients. The present study evaluated the efficacy of nasal turbinate surgery with RF for the treatment of nonallergic rhinitis in elderly patients refractory to medical therapy. Methods: A total of 35 consecutive patients older than 65 years of age (mean subject age, 75.5 ± 9.6 [standard deviation] years) with nonallergic rhinitis refractory to medical therapy who underwent RF turbinate surgery were enrolled in this study. The efficacy of RF turbinoplasty in treating nonallergic rhinitis in elderly patients was evaluated by using rhinoscopy and a visual analog scale score of nasal symptoms. Results: The response rate of primary RF turbinate surgery for nonallergic rhinitis refractory to medical therapy was 68.6%. Postoperative symptom scores for rhinorrhea and nasal obstruction were significantly improved. Persistent crust formation developed in seven patients (20.0%). No patient experienced major complications (e.g., septal hematoma, abscess, septal perforation), but partial bone necrosis was observed in one patient. Conclusion: RF turbinoplasty appeared to be effective for treating some nonallergic rhinitis symptoms in elderly patients, including rhinorrhea and nasal obstruction. These preliminary results are encouraging and warrant further investigation.